Muscle morphology and metabolism in hypothyroid myopathy: effects of treatment. Issue 5 (May 1983) - Khaleeli, A A; Gohil, K; McPhail, G; Round, J M; Edwards, R H
Abstract : Needle biopsies from vastus lateralis in untreated hypothyroid patients with muscle weakness confirmed by quadriceps force measurements (n = 11) were repeated when the patients had taken L-thyroxine for a mean period of 9.2 months (range 5.3-13.3 months, n = 8) and had been continuously biochemically euthyroid for a mean period of 4.9 months (range 2-11 months). Biopsies were analysed biochemically for mitochondrial function. On light microscopy, histochemical examination, mean fibre areas and fibre percentages of type I and type II fibres were determined. Electronmicroscopy was also performed. Abnormalities on light microscopy occurred in eight patients of which type II fibre atrophy was the commonest and of the remainder two patients showed a myopathic electromyogram (EMG) and a raised plasma creatine kinase activity and one ultrastructural change on biopsy. After treatment resolution of pathological changes was often slow and half the patients had persistent abnormalities when rebiopsied. The type I mean fibre area was significantly increased in the eight hypothyroid females (p less than 0.05) and type II mean fibre areas tended to be low and in females this was significant (p less than 0.05). After treatment the type I mean fibre area was significantly reduced (p = 0.05). The type II mean fibre area also tended to fall but this was not significant (p greater than 0.05). No change in the fibre percentages occurred. A myopathic EMG, a raised plasma creatine kinase activity, ultrastructural changes and low mitochondrial enzyme activities on needle biopsy were other common findings and their significance is discussed.